2023
DOI: 10.1038/s41598-023-43672-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between sense of coherence and health and well-being among older survivors of a natural disaster: a prospective outcome-wide study

Hiroyuki Hikichi,
Koichiro Shiba,
Jun Aida
et al.

Abstract: We examined whether pre-disaster Sense of Coherence (SOC) mitigated the impact of housing damage on health and well-being of older survivors after the 2011 Japan Earthquake and Tsunami. A panel survey was conducted in a city located 80 km west of the epicenter seven months before and three years after the disaster (3594 respondents). Among respondents with lighter property damage, higher SOC was inversely associated with mental distress (coefficient − 0.29, 95% CI (confidence interval) − 0.39, − 0.19, p < .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A high and stable SoC is likely to predict better coping in a stressful situation, nevertheless, it might not be enough when faced with a difficult life situation, depending on its severity. A Japanese study investigated the protective nature of SoC among older adults exposed to housing damage due to earthquake and following tsunami in 2011 [ 13 ]. They found that high SoC was protective against high mental distress when exposed to a smaller damage, but not when the exposure was more severe.…”
Section: Introductionmentioning
confidence: 99%
“…A high and stable SoC is likely to predict better coping in a stressful situation, nevertheless, it might not be enough when faced with a difficult life situation, depending on its severity. A Japanese study investigated the protective nature of SoC among older adults exposed to housing damage due to earthquake and following tsunami in 2011 [ 13 ]. They found that high SoC was protective against high mental distress when exposed to a smaller damage, but not when the exposure was more severe.…”
Section: Introductionmentioning
confidence: 99%